Composite fiber solid electrolyte membrane and preparation method and application thereof

By combining the active substance with the modified bacterial cellulose membrane, the composite fiber solid electrolyte membrane was prepared, which solved the shortcomings of the existing sulfide solid electrolyte membrane in terms of flame retardant performance and cycling performance, and achieved the performance improvement of lithium batteries.

CN119725692APending Publication Date: 2025-03-28ZHUJI PAWA NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411960857.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing sulfide solid electrolyte membrane has shortcomings in flame retardant performance and cycling performance, which affects its application in lithium batteries.

Method used

By using the preparation method of a composite fiber solid electrolyte membrane, a film with enhanced mechanical properties and flame retardant properties is formed by combining the active substance Li6PS5Cl and the modified bacterial cellulose membrane.

Benefits of technology

It improves the mechanical properties and flame retardant properties of the solid electrolyte membrane, reduces the crystallinity, and thus improves the circulation and electrochemical properties of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725692A_ABST
    Figure CN119725692A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium battery related materials, and discloses a composite fiber solid-state electrolyte membrane and a preparation method and application thereof.The composite fiber solid-state electrolyte membrane comprises a fiber skeleton and an active substance coating at least part of the surface of the fiber skeleton, the fiber skeleton is an AlPO4 modified bacterial cellulose membrane, and the active substance is an active substance coating at least part of the surface of the fiber skeleton. The active substance is any one or more than two of Li6PS5Cl, Li10GP2S12, Li6PS5Cl < 0.5 > Br < 0.5 >, Li < 5.7 > PS < 4.7 > Cl < 1.3 >. The fiber skeleton provided by the invention can enhance the mechanical property of the solid electrolyte membrane, the flame retardant property of the skeleton modified by aluminum phosphate is enhanced, the crystallinity of the solid electrolyte membrane is reduced, and the cycle performance of the prepared battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium battery related materials and relates to a solid electrolyte membrane, in particular to a composite fiber solid electrolyte membrane and a preparation method and application thereof. Background Art

[0002] In the existing technology, adding LiPF6 to the liquid electrolyte can improve the stability of the battery under high pressure, but the flammability of the liquid electrolyte affects its application prospects. Inorganic solid electrolytes (SE) are more stable under strong impact or high temperature, and their safety performance is better, making them one of the main development directions at present.

[0003] Existing solid electrolytes are mainly divided into three types: oxide solid electrolytes, sulfide solid electrolytes and polymer solid electrolytes. Sulfide solid electrolytes are considered to be a material with broad industrial prospects due to their high ionic conductivity. However, the flame retardancy and cycle performance of sulfide solid electrolyte membranes are poor, which affects the application and development of sulfide solid electrolyte membranes. Summary of the invention

[0004] In view of the defects and shortcomings of the prior art, in the first aspect, the present technical solution provides a composite fiber solid electrolyte membrane; in the second aspect, the present invention provides a method for preparing a composite fiber solid electrolyte membrane; in the third aspect, the present invention provides a battery.

[0005] In a first aspect, the present invention provides a method for preparing a composite fiber solid electrolyte membrane, comprising the following steps: Step 1, mixing bacterial cellulose and citric acid-sodium citrate buffer solution, crushing, and preparing suspension A; mixing active substances, polymers, and solvents to obtain slurry; Step 2, adding aluminum salt, dipotassium hydrogen phosphate and hexamethylenetetramine to suspension A, heating and stirring to react for a certain period of time to obtain suspension B; Step 3, vacuum filtering and drying the suspension B to obtain an AlPO4-modified bacterial cellulose membrane; Step 4, dripping the slurry onto the AlPO4-modified bacterial cellulose membrane and drying it under a protective atmosphere to obtain a composite fiber solid electrolyte membrane.

[0006] Among them, the active materials are Li6PS5Cl, Li 10 GP2S 12 、Li6PS5Cl 0.5 Br 0.5 , Li 5.7 PS 4.7 Cl 1.3 Any one or two or more of the following.

[0007] Preferably, in step 1, the polymer is any one or more of polytetrafluoroethylene, nitrile rubber, polyethylene oxide, and silicone rubber.

[0008] Preferably, in step 1, the solvent is any one or more of toluene, chloroform, anisole and xylene.

[0009] Preferably, in step 1, the pH value of the citric acid-sodium citrate buffer solution is 4-5; and the concentration of the bacterial cellulose membrane in the suspension A is 1.3-3 g / L.

[0010] Preferably, in step 1, the mass ratio of the active substance, the polymer and the solvent in the slurry is 1-2:0.03-0.08:5-8.

[0011] Preferably, in step 2, the molar ratio of the aluminum salt, dipotassium hydrogen phosphate and hexamethylenetetramine added to the suspension A is 1:1-1.2:5-12, and the mass ratio of the bacterial cellulose in the suspension A to the hexamethylenetetramine added to the suspension A is 1:4-15.

[0012] Preferably, the aluminum salt in step 2 is any one or more of aluminum nitrate hexahydrate, aluminum sulfate 18hydrate, and aluminum chloride hexahydrate.

[0013] Preferably, in step 2, the heating temperature is 80-90° C., and the heating reaction time is 6-8 h.

[0014] Preferably, the thickness of the AlPO4-modified bacterial cellulose membrane obtained in step 3 is 80-120 μm.

[0015] Preferably, step 3 also includes washing, and the obtained AlPO4-modified bacterial cellulose membrane is washed 3 to 5 times with deionized water.

[0016] Preferably, in step 3, the drying temperature is 80-100° C. and the drying time is 10-15 hours.

[0017] Preferably, in step 4, 0.5-0.8 g of slurry is dripped onto each square centimeter of the AlPO4-modified bacterial cellulose membrane.

[0018] Preferably, in step 4, the drying temperature is 60-80° C. and the drying time is 5-8 hours.

[0019] Preferably, in step 4, the gas providing the protective atmosphere is any one or both of argon and nitrogen.

[0020] In a second aspect, the present invention provides a composite fiber solid electrolyte membrane, which is prepared by the above-mentioned composite fiber solid electrolyte membrane preparation method; the prepared composite fiber solid electrolyte membrane comprises a fiber skeleton and an active substance coated on at least a part of the surface of the fiber skeleton, wherein the fiber skeleton is an AlPO4-modified bacterial cellulose membrane, and the active substance is Li6PS5Cl, Li 10 GP2S 12 、Li6PS5Cl 0.5 Br 0.5 , Li 5.7 PS 4.7 Cl 1.3 Any one or two or more of the following.

[0021] In a third aspect, the present invention provides a battery comprising the composite fiber solid electrolyte membrane produced by the above-mentioned preparation method.

[0022] Compared with the prior art, the present invention has the following obvious beneficial effects: (1) The fiber skeleton provided by the present invention can enhance the mechanical properties of the solid electrolyte membrane. The flame retardant properties of the skeleton modified by aluminum phosphate are enhanced, the crystallinity of the solid electrolyte membrane is reduced, and the cycle performance of the obtained battery is improved.

[0023] (2) The preparation method of the solid electrolyte membrane provided by the present invention is easy to control and can make aluminum phosphate uniformly coated on the surface of bacterial cellulose, which is beneficial to improving the coating effect and further improving the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a SEM image of the composite fiber solid electrolyte membrane prepared in Example 1; Figure 2 The cycle performance test diagram of the battery assembled with the solid electrolyte membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 2; Figure 3 The time-voltage curve of a Li-Li symmetric battery assembled with the solid electrolyte membrane prepared in Example 1; Figure 4 The time-voltage curve of a Li-Li symmetric battery assembled with the solid electrolyte membrane prepared in Example 2; Figure 5 The time-voltage curve of a Li-Li symmetric battery assembled with the solid electrolyte membrane prepared in Example 3; Figure 6 The time-voltage curve of a Li-Li symmetric battery assembled with the solid electrolyte membrane prepared in Comparative Example 1; Figure 7 The time-voltage curve of the Li-Li symmetric battery assembled with the solid electrolyte membrane prepared in Comparative Example 2; Figure 8 Schematic diagram of the combustion test of the solid electrolyte membrane prepared in Comparative Example 1; Fig. 9 Schematic diagram of the combustion test of the solid electrolyte membrane prepared in Example 1. DETAILED DESCRIPTION

[0025] The present invention provides the following specific technical solutions.

[0026] In a first aspect, the present invention provides a method for preparing a composite fiber solid electrolyte membrane, comprising the following steps: Step 1, mixing bacterial cellulose and citric acid-sodium citrate buffer solution, crushing, and preparing suspension A; mixing active substances, polymers, and solvents to obtain slurry; Step 2, adding aluminum salt, dipotassium hydrogen phosphate and hexamethylenetetramine to suspension A, heating and stirring to react for a certain period of time to obtain suspension B; Step 3, vacuum filtering and drying the suspension B to obtain an AlPO4-modified bacterial cellulose membrane; Step 4, dripping the slurry onto the AlPO4-modified bacterial cellulose membrane and drying it under a protective atmosphere to obtain a composite fiber solid electrolyte membrane.

[0027] Among them, the active materials are Li6PS5Cl, Li 10 GP2S 12 、Li6PS5Cl 0.5 Br 0.5 , Li 5.7 PS 4.7 Cl 1.3 Any one or two or more of the following.

[0028] The inventors have found through research that AlPO4-modified bacterial cellulose membranes can be used as the skeleton of solid electrolyte membranes to enhance the mechanical properties and flame retardancy of solid electrolytes, reduce the crystallinity of solid electrolyte membranes, and help improve the electrochemical performance of batteries. The preparation method provided by the present invention can make aluminum phosphate uniformly coated on the surface of bacterial cellulose membranes, which is beneficial to improving the coating effect and thus improving the electrochemical performance of batteries.

[0029] Preferably, the polymer is any one or more of polytetrafluoroethylene, nitrile rubber, polyethylene oxide, and silicone rubber.

[0030] Preferably, the solvent is any one or more of toluene, chloroform, anisole and xylene.

[0031] Preferably, in step 1, the pH value of the citric acid-sodium citrate buffer solution is 4-5; and the concentration of the bacterial cellulose membrane in the suspension A is 1.3-3 g / L.

[0032] Preferably, in step 1, the mass ratio of the active substance, the polymer and the solvent in the slurry is 1-2:0.03-0.08:5-8.

[0033] Preferably, in step 2, the molar ratio of the aluminum salt, dipotassium hydrogen phosphate and hexamethylenetetramine added to the suspension A is 1:1-1.2:5-12, and the mass ratio of the bacterial cellulose in the suspension A to the hexamethylenetetramine added to the suspension A is 1:4-15.

[0034] Preferably, the aluminum salt in step 2 is any one or more of aluminum nitrate hexahydrate, aluminum sulfate 18hydrate, and aluminum chloride hexahydrate.

[0035] Preferably, in step 2, the heating temperature is 80-90° C., and the heating reaction time is 6-8 h.

[0036] Preferably, the thickness of the AlPO4-modified bacterial cellulose membrane obtained in step 3 is 80-120 μm.

[0037] Preferably, step 3 also includes washing, and the obtained AlPO4-modified bacterial cellulose membrane is washed 3 to 5 times with deionized water.

[0038] Preferably, in step 3, the drying temperature is 80-100° C. and the drying time is 10-15 hours.

[0039] Preferably, in step 4, 0.5-0.8 g of slurry is dripped onto each square centimeter of the AlPO4-modified bacterial cellulose membrane.

[0040] Preferably, in step 4, the drying temperature is 60-80° C. and the drying time is 5-8 hours.

[0041] Preferably, in step 4, the gas providing the protective atmosphere is any one or both of argon and nitrogen.

[0042] In a second aspect, the present invention provides a composite fiber solid electrolyte membrane, which is prepared by the above-mentioned composite fiber solid electrolyte membrane preparation method; the prepared composite fiber solid electrolyte membrane comprises a fiber skeleton and an active substance coated on at least a part of the surface of the fiber skeleton, wherein the fiber skeleton is an AlPO4-modified bacterial cellulose membrane, and the active substance is Li6PS5Cl, Li 10 GP2S 12 、Li6PS5Cl 0.5 Br 0.5 , Li 5.7 PS 4.7 Cl 1.3 Any one or two or more of the following.

[0043] In a third aspect, the present invention provides a battery comprising the composite fiber solid electrolyte membrane produced by the above-mentioned preparation method.

[0044] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0045] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0046] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0047] Embodiment 1: A method for preparing a composite fiber solid electrolyte membrane comprises the following steps: Step 1, weigh 50 mg of bacterial cellulose membrane, add it into 25 mL of citric acid-sodium citrate buffer solution with a pH value of 5, and break up the BC with a high shear emulsifier to prepare suspension A.

[0048] Step 2, add 0.13g Al(NO3)3·6H2O powder, 0.7g K2HPO4 powder and 0.6g hexamethylenetetramine to the suspension, heat to 90°C and stir to react for 6h to obtain suspension B.

[0049] Step 3, pour the suspension B into a vacuum filtration device for filtration. After the filtration is completed, the membrane formed at the bottom of the filtration funnel is the AlPO4-modified bacterial cellulose membrane, which is washed several times with deionized water and placed in an oven at 90°C for 10 hours.

[0050] Step 4: 4 g of Li6PS5Cl powder and 0.12 g of polytetrafluoroethylene are added to 12 g of toluene to form a slurry.

[0051] Step 5, place the bacterial cellulose / AlPO4 composite fiber membrane on a glass plate, drop 15g of the slurry obtained in step 4 onto the 5×5cm bacterial cellulose / AlPO4 composite fiber membrane, and then transfer the glass plate to an Ar-filled glove box to evaporate the solvent, and then transfer it to a 80°C vacuum oven for drying for 8h to obtain a composite fiber solid electrolyte membrane.

[0052] Figure 1 is a SEM image of the composite fiber solid electrolyte membrane prepared in Example 1. Figure 1 It can be seen that the dot-like particles are evenly distributed on the fiber surface, indicating that the active substances are evenly coated on the fiber surface.

[0053] Comparative Example 1: A method for preparing a composite fiber solid electrolyte membrane comprises the following steps: Step 1, adding 2 g of Li6PS5Cl powder and 0.06 g of polytetrafluoroethylene to 6 g of toluene to form a slurry; Step 2, drip 5 g of the slurry obtained in step 1 onto a 5×5 cm bacterial cellulose membrane, then transfer the glass plate to an Ar-filled glove box to evaporate the solvent, and then transfer it to a vacuum oven at 80° C. for drying for 8 hours to obtain a composite fiber solid electrolyte membrane.

[0054] Comparative Example 2: Step 1, 4 g Li6PS5Cl powder and 0.12 g polytetrafluoroethylene are added to 12 g toluene to form a slurry; Step 2, take 15g of the slurry obtained in step 1 and apply it to a glass plate with a 500μm scraper, then transfer the glass plate to a glove box filled with Ar to evaporate the solvent, and then transfer it to a vacuum oven at 80°C for drying for 8h to obtain a sulfide solid electrolyte membrane.

[0055] Embodiment 2: A method for preparing a composite fiber solid electrolyte membrane comprises the following steps: Step 1, weigh 35 mg of bacterial cellulose membrane, add it into 25 mL of citric acid-sodium citrate buffer solution with a pH value of 4, and break up the BC with a high shear emulsifier to prepare suspension A.

[0056] Step 2, add 0.067g Al2(SO4)3·18H2O powder, 0.042g K2HPO4 powder and 0.15g hexamethylenetetramine to the suspension, heat to 90°C and stir to react for 6h to obtain suspension B.

[0057] Step 3, pour the suspension B into a vacuum filtration device for filtration. After the filtration is completed, the membrane formed at the bottom of the filtration funnel is the AlPO4-modified bacterial cellulose membrane, which is washed several times with deionized water and placed in an oven at 80°C for 10 hours.

[0058] Step 4: 2 g of Li6PS5Cl powder and 0.06 g of polytetrafluoroethylene are added to 16 g of toluene and mixed to form a slurry.

[0059] Step 5, place the bacterial cellulose / AlPO4 composite fiber membrane on a glass plate, drop 12.5g of the slurry obtained in step 4 onto the 5×5cm bacterial cellulose / AlPO4 composite fiber membrane, and then transfer the glass plate to an Ar-filled glove box to evaporate the solvent, and then transfer it to a 80°C vacuum oven for drying for 8h to obtain a composite fiber solid electrolyte membrane.

[0060] Embodiment 3: A method for preparing a composite fiber solid electrolyte membrane comprises the following steps: Step 1, weigh 75 mg of bacterial cellulose membrane, add it into 25 mL of citric acid-sodium citrate buffer solution with a pH value of 5, and break up the BC with a high shear emulsifier to prepare suspension A.

[0061] Step 2, add 0.15g AlCl3·6H2O powder, 0.12g K2HPO4 powder and 1.0g hexamethylenetetramine to the suspension, heat to 90°C and stir to react for 6h to obtain suspension B.

[0062] Step 3, pour the suspension B into a vacuum filtration device for filtration. After the filtration is completed, the membrane formed at the bottom of the filtration funnel is the AlPO4-modified bacterial cellulose membrane, which is washed several times with deionized water and placed in an oven at 100°C for 10 hours.

[0063] Step 4: 6 g of Li6PS5Cl powder and 0.18 g of polytetrafluoroethylene are added to 18 g of toluene and mixed to form a slurry.

[0064] Step 5, place the bacterial cellulose / AlPO4 composite fiber membrane on a glass plate, drop 20g of the slurry obtained in step 4 onto the 5×5cm bacterial cellulose / AlPO4 composite fiber membrane, and then transfer the glass plate to an Ar-filled glove box to evaporate the solvent, and then transfer it to a 80°C vacuum oven for drying for 8h to obtain a composite fiber solid electrolyte membrane.

[0065] Preparation of positive electrode sheet: The positive electrode active material, lithium nickel cobalt manganese oxide (NCM), sulfide solid electrolyte, conductive carbon black and binder PVDF are mixed in a ratio of 70:25:1:4, and ground and mixed to obtain positive electrode powder. The positive electrode powder is dissolved in dimethyl ether, and the mass ratio of the positive electrode powder to dimethyl ether is 2:5. After magnetic stirring, it is coated on aluminum foil to obtain a positive electrode sheet.

[0066] The solid electrolyte membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were cut into discs with a diameter of 16 mm, and then added into a polyetheretherketone (PEEK) resin mold (diameter: 16 mm). The solid electrolyte membranes were pressed into sheets by a sheet press, the pressure was set to 300 MPa, and the pressure holding time was 5 min. The composite electrolyte material obtained after pressing was a solid electrolyte membrane, and a lithium-indium alloy sheet was used as the negative electrode sheet. The solid electrolyte membrane, the positive electrode sheet, and the negative electrode sheet were respectively cut into discs with diameters of 16 mm, 12 mm, and 12 mm by a slicer to assemble a sandwich structure button-type solid-state battery.

[0067] The battery cycle performance was tested in the following manner: the assembled button cell was charged and discharged twice at a rate of 0.1C using a battery charge and discharge tester (model CT3002A) from Wuhan Blue Electric Company, and then the charge and discharge cycle test was performed at a rate of 0.3C. The test temperature was 25°C and the voltage range was 2.8~4.3V.

[0068] Figure 2 The cycle performance test diagram of the battery assembled with the solid electrolyte membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 is shown in FIG. Figure 2 It can be seen that Example 1, Example 2 and Example 3 all show high initial capacity and stable capacity cycle, and Comparative Example 1 and Comparative Example 2 both have a large degree of capacity decay, indicating that after adding the modified bacterial cellulose membrane as the skeleton of the sulfide solid electrolyte, the transmission of lithium ions is greatly promoted, allowing the battery to maintain a stable cycle for a long time.

[0069] The solid electrolyte membranes and lithium sheets prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were made into Li-Li symmetrical batteries. -2 At a current density of 25°C and a test temperature of 25°C, electroplating / stripping cycles were carried out with each cycle lasting 1 hour to test the cyclic stability of the composite solid electrolyte membrane and the lithium metal electrode.

[0070] from Figures 3 to 7 The electroplating / stripping cycle test diagrams of Li-Li symmetrical batteries assembled from solid electrolyte membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 2 are shown in order. Figures 3 to 7 It can be seen that during the charge and discharge cycle, Examples 1 to 3 have relatively lower overpotentials than Comparative Examples 1 to 2, and the overpotentials of Comparative Examples 1 and 2 continue to increase as the cycle proceeds, indicating that ion diffusion is hindered and the internal resistance continues to increase. Comparative Example 2 experienced voltage instability after 280 hours, which may be caused by lithium dendrite puncture. Therefore, by adding a modified bacterial cellulose membrane as a skeleton to the sulfide solid electrolyte, the cycle stability and mechanical strength of the battery can be increased, the formation of lithium dendrites can be inhibited, and the lithium ion transmission efficiency can be improved.

[0071] Figure 8 and Fig. 9 Schematic diagrams of the combustion test of the solid electrolyte membranes prepared in Comparative Example 1 and Example 1, respectively. Figure 8 It can be seen that the solid electrolyte membrane prepared in Comparative Example 1 burns when heated; Fig. 9 It can be seen that the solid electrolyte membrane prepared in Example 1 cannot be ignited, which proves that the flame retardant property of the composite solid electrolyte membrane provided by the present invention is enhanced.

[0072] The embodiments described above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope of the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a composite fiber solid electrolyte membrane, characterized in that: The steps include: Step 1, mixing bacterial cellulose and citric acid-sodium citrate buffer solution, crushing, and preparing suspension A; mixing active substances, polymers, and solvents to obtain slurry; Step 2, adding aluminum salt, dipotassium hydrogen phosphate and hexamethylenetetramine to suspension A, heating and stirring to react for a certain period of time to obtain suspension B; Step 3, vacuum filtering and drying the suspension B to obtain an AlPO4-modified bacterial cellulose membrane; Step 4, dripping the slurry onto the bacterial cellulose membrane modified with AlPO4, and drying it under a protective atmosphere to obtain a composite fiber solid electrolyte membrane; Among them, the active materials are Li6PS5Cl, Li 10 GP2S 12 、Li6PS5Cl 0.5 Br 0.5 , Li 5.7 PS 4.7 Cl 1.3 Any one or two or more of the following.

2. The method for preparing a composite fiber solid electrolyte membrane according to claim 1, characterized in that: In step 1, the polymer is any one or more of polytetrafluoroethylene, nitrile rubber, polyethylene oxide, and silicone rubber; and the solvent is any one or more of toluene, chloroform, anisole, and xylene.

3. The method for preparing the composite fiber solid electrolyte membrane according to claim 1, characterized in that: In step 1, the pH value of the citric acid-sodium citrate buffer solution is 4-5; the concentration of the bacterial cellulose membrane in the suspension A is 1.3-3 g / L.

4. The method for preparing a composite fiber solid electrolyte membrane according to claim 1, characterized in that: In step 1, the mass ratio of the active substance, the polymer and the solvent in the slurry is 1-2:0.03-0.08:5-8.

5. The method for preparing a composite fiber solid electrolyte membrane according to claim 1, characterized in that: In step 2, the molar ratio of the aluminum salt, dipotassium hydrogen phosphate and hexamethylenetetramine added to the suspension A is 1:1~1.2:5~12, and the mass ratio of the bacterial cellulose in the suspension A to the hexamethylenetetramine added to the suspension A is 1:4~15; the aluminum salt in step 2 is any one or more of aluminum nitrate hexahydrate, aluminum sulfate 18hydrate and aluminum chloride hexahydrate.

6. The method for preparing a composite fiber solid electrolyte membrane according to claim 1, characterized in that: In step 2, the heating temperature is 80-90°C, and the heating reaction time is 6-8h; in step 3, the drying temperature is 80-100°C, and the drying time is 10-15h.

7. The method for preparing a composite fiber solid electrolyte membrane according to claim 1, characterized in that: In step 4, 0.5-0.8 g of slurry is added dropwise to each square centimeter of the AlPO4-modified bacterial cellulose membrane.

8. The method for preparing a composite fiber solid electrolyte membrane according to claim 2, characterized in that: In step 4, the drying temperature is 60-80° C., and the drying time is 5-8 hours; the gas providing the protective atmosphere is either argon or nitrogen, or both.

9. A composite fiber solid electrolyte membrane, characterized in that: The composite fiber solid electrolyte membrane is prepared by the preparation method of any one of claims 1 to 8; the prepared composite fiber solid electrolyte membrane comprises a fiber skeleton and an active substance coated on at least part of the surface of the fiber skeleton, wherein the fiber skeleton is an AlPO4-modified bacterial cellulose membrane, and the active substance is Li6PS5Cl, Li 10 GP2S 12 、Li6PS5Cl 0.5 Br 0.5 , Li 5.7 PS 4.7 Cl 1.3 Any one or two or more of the following.

10. A battery, characterized in that: It comprises a composite fiber solid electrolyte membrane prepared by the preparation method described in claims 1 to 8.